A century of holiness theology : the doctrine of entire sanctification in the Church of the Nazarene : 1905 to 2004 - Quanstrom, Mark R., 1955- (Kansas City, Mo. : Beacon Hill Press of Kansas City, 2013)
Traces the development of the doctrine of entire sanctification as practiced by the Church of the Nazarene. Describes the doctrine as proclaimed by John Wesley in the eighteenth century and the circumstances that have led to its adjustment in the twentieth century.
Includes bibliographical references.
Print version record.
Keywords: Church of the Nazarene -- Doctrines -- History -- 20th century; Holiness -- Church of the Nazarene -- History of doctrines -- 20th century; Sanctification -- Church of the Nazarene -- History of doctrines -- 20th century; RELIGION / Christian Theology / Soteriology; Electronic books